Educational Gamification for The Enhancement of Student Motivation - Amir, Rizqina Kautsarani Amira Putri (EDULANGUE, 2024)
Gamification is a method used to support the learning process in a non-game environment. The aim of this study is to explore how to implement gamification in education to increase students' learning motivation, the most effective elements in increasing student learning motivation in educational contexts, and students' experiences in interacting with educational games that affect student learning motivation. The participants were 25 junior school students who had experience using educational games for learning. Data from questionnaires and interviews were collected to determine students' perceptions of their experiences in using educational games. Self-determination theory (SDT) was used to evaluate students' motivation to learn English. The results show that gamification has the potential to increase students' interest and engagement in learning English, which in turn increases students' motivation to participate in learning. Gamification creates a fun learning experience for students. Intrinsic and extrinsic motivation also emerged from within students during gamified learning. In this study, students have a positive attitude toward the use of educational gamification in the classroom.